Development of PBL-Based Module to Facilitate Students’ Science Literacy and Independence Skills (Unnes Science Education Journal, 2022)
The purpose of this study is to develop a respiratory system module, test its feasibility and practicality, and analyze the module potential to train students' scientific literacy skills and independence. The feasibility test is carried out through expert-judgment by experts and the module's readability test. The module practicality is measured by the responses of students and biology teachers. The potential of the module in practicing scientific literacy and student independence was obtained from the results of posttest and observations. The results showed that the feasibility level of the module according to material and media experts was 71,67% and 78,12% (feasible). The readability of the module according to students is 79% (feasible). The level of practicality of the module according to students and teachers are 82,27% and 96,15% (very practical). The results of the posttest and observation showed that the scientific literacy level of the experimental class reached 61.46% and for the control class was only 52,53%. The average independence of the experimental and control class are 61,84% and 53,14%. Conclusion: The respiratory system material module is feasible and practical to be applied in learning, and has the potential to train students' scientific literacy skills and independence.